1999
DOI: 10.1117/12.350057
|View full text |Cite
|
Sign up to set email alerts
|

<title>Electroviscous effects in microchannels</title>

Abstract: Fluid flow in capillary microchannels is used in numerous applications in biotechnology (such as protein separation, fast DNA analysis, drug deliveries systems and viral filtration), in solid-state devices, and in catalytic devices. The current work presents the experimental validation for the electrokinetic theory in microchannels. Retardation of polar liquids, including de-ionized water, ethanol and propyl alcohol, is studied in microfabricated channels of several diameters.It was found that polar liquids fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 3 publications
1
11
0
Order By: Relevance
“…Electroviscous effects of polar liquids in micron-sized channels is well documented. 10,11 In any case, this would result in an effective tube diameter, D eff ϭDϪ, were is the peak-to-valley roughness height. Using the data in Table I, the 30 gage tube would have an effective diameter of 159.5 m, rather than 163.5 m, corresponding to a 10% increase in Po.…”
Section: Discussionmentioning
confidence: 99%
“…Electroviscous effects of polar liquids in micron-sized channels is well documented. 10,11 In any case, this would result in an effective tube diameter, D eff ϭDϪ, were is the peak-to-valley roughness height. Using the data in Table I, the 30 gage tube would have an effective diameter of 159.5 m, rather than 163.5 m, corresponding to a 10% increase in Po.…”
Section: Discussionmentioning
confidence: 99%
“…Well-controlled recent experiments have clearly confirmed that it can explain the behaviour of the Poiseuille number in the laminar regime, providing that the liquid contains a very small amount of ions [20]. Kulinsky et al [11] reported an increase of 70% of the friction factor under the EDL effect in planar channels of 4 µm heights with distilled water. Large thickness of the diffuse EDL layer of about 1 µm or more have been reported in these experiments.…”
Section: Introductionmentioning
confidence: 88%
“…Although the experiments on the EDL effect are few, its effects were proved. Kulinsky et al [66] reported an increment of 70% of the friction factor under the EDL effect in planar channels of 4 μm height with distilled water. Ren et al [67] made well-controlled experiments with three silicon channels with a height of 14.1, 29.2 and 40.5 µm and de-ionized ultra-filtered water and aqueous KCl.…”
Section: The Electrical Double Layer Effect On Flow and Heat Transfermentioning
confidence: 98%